Stature and Its Estimation Utilizing Arm Span Measurements of both gender Adolescents from Southern Region in Kosovo - Fitim Arifi; Sami Sermaxhaj; Jovan Gardasevic; Iber Alaj; Zenel Metaj (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
This study is based on measurements of Southern region Kosovan adolescents. The aim of this study was to examine the stature of adolescents from Southern region as well relationship between arm span and stature in both Kosovar genders. A total measured subject participated in this research was 225 out of which (105 girls and 120 boys), females average of age is 18.36±0.50 years old (range 18-20 years) and for male 18.40±0.55 years old (range 18-20 years).The anthropometric measurements were done by trained people and were taken according to the ISAK manual. Relationship between stature and arm span has been analyzed by the simple correlation coeffi cient at a 95% confi dence interval. The linear regression analysis was carried out to examine extent to which arm span can reliably predict of stature. Statistical importance was placed at level p<0.05. As a result anthropometric measurements for both sexes showed that the average of stature for boys adolescents from Southern region are 178.60±5.73 centimeters and have the arm span average of 180.92±6.92 centimeters, while girls from Southern 165.33±4.45 centimeters tall, and have the arm span average of 165.60±6.03 centimeters. The results have shown that the arm span was estimated as a reliable indicator of stature assessment to the both genders adolescents from Southern region of Kosovo population. This study also confi rms the necessity for developing separate height models for each region in Kosovo.